Réponses

2014-09-21T14:32:48+02:00
Résoudre les système suivants

1)
2x + 3y = 5
-3x + y = 1

2x + 3y = 5
9x - 3y - 3
11x = 2
x = 2/11

- 3x + y = 1
- 3 * 2/11 + y = 1
- 6/11 + y = 1
11y/11 = 11/11 + 6/11
11y = 17
y = 17/11

Les solutions sont : (2/11 ; 17/11)

2)
4t - 3u = 1/2
- 3/2t + u = - 2

4t - 3u = 1/2
- 9/2t + 3u = - 6

8/2t  - 6/2u = 1/2
- 9/2t + 6/2u = - 12/2
- 1/2t = - 11/2
t = 11

4t - 3u = 1/2
4 * 11 - 3u = 1/2
44 - 3u = 1/2
- 3u = 1/2 - 44
- 6/2u =1/2 - 88/2
6u = 87
u = 87/6
u = 14,5

Les solutions sont : (11 ; 14,5)